2003
DOI: 10.1103/physrevb.67.094419
|View full text |Cite
|
Sign up to set email alerts
|

Induced Fe and Mn magnetic moments in Co-FeMn bilayers on Cu(001)

Abstract: Using photoemission electron microscopy in combination with x-ray magnetic circular dichroism, element selective magnetic domain images have been obtained from single-crystalline Co/FeMn and FeMn/Co bilayers epitaxially grown on a Cu(001) single crystal. The contact with ferromagnetic Co leads to the observation of a net magnetic moment in Fe and Mn, independently of the paramagnetic or antiferromagnetic state of the FeMn thin films. Only a small fraction of this moment might mediate the magnetic interaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 34 publications
(29 reference statements)
4
52
0
Order By: Relevance
“…This size of induced ferromagnetic alignment is consistent with our earlier investigation of FeMn/Co bilayers. 19 Furthermore, the Fe XMLD originating from induced moments at the interface decreases with increasing total FeMn thickness, so that the expected Fe XMLD signal would be within the noise of the measurement of the spectra of Ref. 21, which were taken for a 15 ML FeMn film.…”
mentioning
confidence: 98%
“…This size of induced ferromagnetic alignment is consistent with our earlier investigation of FeMn/Co bilayers. 19 Furthermore, the Fe XMLD originating from induced moments at the interface decreases with increasing total FeMn thickness, so that the expected Fe XMLD signal would be within the noise of the measurement of the spectra of Ref. 21, which were taken for a 15 ML FeMn film.…”
mentioning
confidence: 98%
“…The strength of the uniaxial anisotropy in our CoO/Fe/Ag(001) system after field cooling is above 3000 Oe, which is much greater than the previous experimental data. This may be due to the epitaxial growth nature of our sample and the strong CoO magnetic anisotropy (~2.7×10 8 erg/cm 3 [53] FeMn/Co/Cu(001) system and was attributed to step-induced uncompensated spins at the AFM surface [44,45,46]. We don't know if the same mechanism accounts for the CoO/Fe/Ag(001) system.…”
Section: Resultsmentioning
confidence: 82%
“…The exchange bias field obtained directly from the easy-axis hysteresis loop measurement is also shown in Fig. 3 The switching of the 4-fold anisotropy easy axis in AFM/FM system was also reported in other AFM/FM system [44,45,46] and was attributed to the interfacial spin frustration. This result is consistent with our previous result [31].…”
Section: Resultsmentioning
confidence: 97%
“…Applying the field in-plane yielded no signal. On the other hand XMCD (X-ray Magnetic Circular Dichroism) experiments have shown that for the system Fe x Mn 1−x /Co/Cu(100) 'uncompensated' Fe spins exist [4]. On the basis of these observations we used a perpendicular magnetized 25 ML Ni/Cu(100) as a substrate.…”
Section: Introductionmentioning
confidence: 97%